International accounting: towards its harmonization - Ali, Rozaimah (1992)
In the international market, there is active selling and buying of shares, foreign investment and borrowing especially through the existence of multinational companies. If financial measurement standards are to be made more meaningful, one of the first issues to be confronted is the need for harmonization. Accounting itself is the product of disparate of sociological, economic and political factors. Therefore accounting in Europe, America, Africa and Asian has deep-rooted differences. If all the international organizations can do effective research in a comprehensive manner, harmonization might be achieved. A way must be created for a bilateral action and support.